Development of DNA-based dynamic key-dependent block cipher - Saeed, Auday H. (2015)
The need for an extremely effective means of achieving information security is constantly necessary and indispensable. The cryptographic algorithm is one of the strongest tools for providing appropriate security for systems and data transmissions. The symmetric block cipher is one of the most significant cryptographic algorithms. It is essential for institutions to build their own symmetric block cipher to address the newly emerging threats that are the result of new technologies. Hence, it is necessary to research and develop a secure symmetric cipher algorithm. Since the declaration of Rijndael as AES this cipher has been the target of many attacks, and the attempts to break it are ongoing and even increasing everyday by taking advantage of the rapid development in computing capabilities. The rise in the frequency of attacks against the AES has ot been matched by the level of development in the capabilities of the algorithm to withstand these challenges and make the AES secure and immune to all risks. The byte substitution and permutation units in AES block cipher which produce diffusion and confusion have fixed structure for all rounds. This thesis proposes a new secure symmetric block cipher called DNA-Based Block Cipher (DNAB), with key-dependent components inspired by DNA biology techniques. The thesis identifies the similarity elements, and highlights the essential computation elements, namely the DNA-strands, DNA-bases, Central dogma process that can be applied in symmetric block cipher that fulfills Shannon’s confusion and diffusion properties. The DNAB utilizes the DNA-based key-dependent components to enhance the security of cipher, and reduce the number of cipher-iterated rounds. Accordingly,for the substitution layer, the reality that the S-Boxes are unknown is one of the major strengths of the new cipher as the cryptanalysis requires known S-Boxes. For the permutation layer the use of key-dependent ransformations and processes inspired by DNA techniques forces the attackers to try and devise hard new frameworks of cryptanalytic mechanisms. The experimental findings presented the randomness of the output in the DNAB cipher, as secure cipher, and compared to AES, the number of iteration rounds is reduced. The S-Box tests criteria presenting the new S-Boxes in DNAB cipher satisfy the balance, completeness, avalanche, strict avalanche, itindependence,nonlinearity, differential-uniformity, invertability and noncontradiction criteria as good S-Box conditions. The avalanche effect, correlation coefficient, bit error and key sensitivity of the DNAB cipher were laboratory tested, and they satisfied the confusion and diffusion properties. In spite of the fact that the S-Boxes of DNAB cipher have 8 bits for input and output, the output has the possibility of one of the 2n1 compared to 2-8 possibilities for the static S-Box; also for each round, keydependent and MixColumns transformations has (2-8, 2-4) possibilities each. This makes the cryptanalysis of these transformations difficult since it needs cryptanalysts to construct all the possibilities. It was confirmed that the DNAB cipher had successfully passed very demanding security analyses and justified that the DNAB cipher is a secure block-cipher. Accordingly, it will increase the protection of institutional information systems; also it will be considered as one of a symmetric block ciphers in information security research, and open the doors to matchmaking between computer security and biological systems research.